Composition of Trap Net (Gombang) Catch Based on Tidal Conditions in Insit Village, Meranti Islands Regency - M. Febrian Fadli; Alit Hindri Yani (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Trap nets (gombang) are passive fishing gears that utilize tidal currents to capture fish and shrimp in coastal waters. This study aims to identify the composition of catches from trap nets based on tidal conditions in the waters of Insit Village, Meranti Islands Regency. The research method used was a survey method through direct observation and interviews with fishermen. Data analysis was carried out using catch-proportion analysis, including main catch, by-catch, and discards. The results showed that penaeid shrimp and small pelagic fish such as anchovies dominated the catch composition. Catch composition was influenced by tidal conditions, where catches during high tide were higher than during low tide. The catch proportions indicate that trap nets still exhibit low selectivity, as evidenced by the high by-catch rate. Therefore, better management is needed to improve the efficiency and sustainability of trap net fisheries in the area.